Multiple distinct subtypes of GABAergic neurons in mouse visual cortex identified by triple immunostaining - Gonchar, Yuri; Wang, Quanxin; Burkhalter, Andreas H. (Frontiers in Neuroanatomy, 2008)
The majority of cortical interneurons use GABA (gamma amino butyric acid) as inhibitory neurotransmitter. GABAergic neurons are morphologically, connectionally, electrically and chemically heterogeneous. In rat cerebral cortex three distinct groups of GABAergic interneurons have been identifi ed by the expression of parvalbumin (PV), calretinin (CR) and somatostatin (SOM). Recent studies in mouse cerebral cortex have revealed a different organization in which the CR and SOM populations are partially overlapping. Because CR and SOM neurons derive from different progenitors located in different embryonic structures, the coexpression of CR + SOM suggests that the chemical differentiation of interneurons is regulated postmitotically. Here, we have taken an important fi rst step towards understanding this process by triple immunostaining mouse visual cortex with a panel of antibodies, which has been used extensively for classifying developing interneurons. We have found at least 13 distinct groups of GABAergic neurons which include PV, CR, SOM, CCK (cholecystokinin), CR + SOM, CR + NPY (neuropeptide Y), CR + VIP (vasointestinal polypeptide), SOM + NPY, SOM + VIP, VIP + ChAT (choline acetyltransferase), CCK + NPY, CR + SOM + NPY and CR + SOM + VIP expressing cells. Triple immunostaining with PV, CR and SOM antibodies during postnatal development further showed that PV is never colocalized with CR and SOM. Importantly, expression of SOM and CR + SOM developed after the percentage of CR cells that do not express SOM has reached the mature level, suggesting that the chemical differentiation of SOM and CR + SOM neurons is a postnatal event, which may be controlled by transcriptional regulation.